The effects of conflict-induced migration on food security and health related outcomes in Sudan: From displacement to despair - Abushama, Hala; Kirui, Oliver K.; Taffesse, Alemayehu Seyoum; Siddig, Khalid; Mohamed, Shima A. H. (International Food Policy Research Institute, 2024)
This study investigates the socioeconomic effects of conflict-induced migration in Sudan, focusing on the food security and access to healthcare of displaced households. Triggered by the civil conflict that started in April 2023, the recent widespread displacement of households has intensified vulnerabilities across the country. Using three datasets—the pre conflict 2022 Sudan Labor Market Panel Survey and two surveys conducted during the conflict, the 2023/24 Sudan Rural Household Survey and the 2024 Sudan Urban Household Survey—the research examines the impacts on household food security and healthcare access of migration driven by conflict. The study employs inverse probability weighting to estimate the causal impacts of migration, leveraging data from over 12,000 households. The key impact indicators at the household level were the Food Insecurity Experience Scale score and, as a measure of healthcare access, any incidence of illness in the household. Analysis shows that migration induced by conflict exacerbates food insecurity, with over 90 percent of rural households and nearly 80 percent of urban households reporting moderate to severe food insecurity. Rural households face additional challenges as displacement disrupts agricultural livelihoods and access to markets. Migration also worsens healthcare access, particularly in rural areas where displaced households experience a higher likelihood of illness. For urban households, migration fails to alleviate their healthcare challenges due to the collapse of urban healthcare systems. The study calls for urgent policy interventions, including targeted food aid and mobile healthcare services. Restoring healthcare infrastructure, expanding social protection mechanisms, and fostering peacebuilding efforts are critical to mitigating future displacement and supporting socioeconomic recovery. These findings offer valuable insights for policymakers and humanitarian actors to address the immediate and long-term needs of displaced populations in Sudan.